Study of Trichoderma as a biocontrol agent on selected diseases of ornamental foliage plants in Sri Lanka - Jegathambigai, V. (Faculty of Science, University of Colombo, 2011)
Several species of the fungus, Trichoderma were isolated from organic rich soil samples obtained from Green Farms Limited (Ornamental foliage nursery), Marawila, Sri Lanka. The fungal species were identified based on their morphological, reproductive and molecular characteristics. On the basis of DNA sequence data analysis, the isolates were identified as Trichoderma viride strain NRRL 6418, Trichoderma asperellum strain Dll, Trichoderma sp. Hy6, Trichoderma sp. ZAUT013 and Hypocrea lixii isolate TWC{{Trichoderma harzianum). The efficacy of locally isolated Trichoderma species to control three soil borne plant pathogens and one plant parasitic nematode were studied under in vitro and in vivo conditions. The influence of environmental factors on the mycelia growth of the Trichoderma spp and the survival of the Trichoderma spp in normal field soil and in different organic substrates were studied. The phytotonic effect of Trichoderma spp on plant growth was also investigated. The investigation was also extended to evaluate the selected Trichoderma spp against regular pesticides and fertilizer mixtures. The native isolates had antagonistic effects against the soil borne plant pathogens, Helminthosporium (Bipolaris) spp, Sclerotium rolfsii, Fusarium oxysporum, and plant parasitic nematode Meloidogyne incognita. S. rolfsii and F. oxysporum are causative fungi of collar rot on Zamioculcas zamiifolia and vascular wilt on Crossandra infundibidiformis respectively. Helminthosporium, spp complex is the causative agent of leaf spot on Dypsis lutescens. M. incognita is the causative agent of root knot on Livistona rotundifolia. T. viride NRRL 6418 was able to control S. rolfsii collar rot disease incidence in Z. zamiifoila, whereas T. asperellum D11 was able to control F. oxysporum wilt in C. infundibidiformis, while T. viride NRRL and H. lixii TWC1 mixture were able to control leaf spot caused by Helminthosporium spp complex on D. lutescens respectively. H. lixii TWC1 (T. harzianum) and T. viride NRRL 6418 were able to control root knot nematode M. incognita infecting L. rotundifolia. The three most effective isolates were T. viride NRRL, T. asperellum D11 and H. lixii TWC1 (T. harzianum). Trichoderma treatment significantly (*p<0.05) enhanced growth of shoot, root and seed germinations of ornamental foliage plants when compared to untreated plants. Different growth media such as Pleurotus ostreatus mushroom compost media, regular farm compost media, coir media and Ca (NC^ treated coir media were evaluated for thensuitability to support the spore production of Trichoderma spp under field conditions. Mushroom compost media yielded the highest spore load of Trichoderma spp which was superior to other growing media. Regular farm compost was next best to support good spore development of Trichoderma spp. Normal coir and Ca (N03)2 treated coir media did not support good spore development of the Trichoderma spp. Protocol for on-Farm mass production of these isolates of Trichoderma spp was developed to help facilitate the establishment of an integrated eco-friendly disease management system for growers. The media evaluated in this study included the solid substrates barley seeds, paddy, cowpea (two varieties), maize and sorghum and semi-solid or liquid substrates such as potato dextrose, rice extract, paddy extracts respectively. Mycelia growth was fastest in parboiled barley and paddy media, the highest yield of spores of the Trichoderma isolates was also observed seven days after inoculation in barley and paddy media.
Keywords: Trichoderma, soil-borne disease, parasitic nematodes, ornamental foliage plants.